Relationship Between Students’ Self-efficacy, Gender and Academic Achievement in Information and Communication Technology in Anambra State - Okekeokosisi, JohnBosco O.C.; Nchikwo, Nkechi T.; Ezzeh, Peace O. (International Journal of Computing Sciences Research; Vol 7 (2023): Volume 7, 2023)
Purpose – The need to ascertain if there is any other factor responsible for the poor achievement of students in ICT necessitated the study. This study aimed to investigate the relationship between students' self-efficacy, gender, and their academic achievement in ICT in Anambra State. Methods – The design of the study was a correlational survey research design. The study was guided by three research questions and three null hypotheses. The study was carried out in co-educational schools of two selected education zones that are among the six education zones in which ICT as a subject was offered in external examination and are co-educational public schools. The sample of the study consists of 473 senior secondary two (SS2) ICT students drawn from schools from two education zones that offer ICT in WAEC. The general self-efficacy instrument of Schawarzar and Mathias (1979) was adopted by the researchers. The reliability coefficient of 0.76 to 0.90 was used.  Person's product-moment correlation coefficient was used to answer the research questions while multiple regression was used to test the null hypotheses. Results – The result of the study revealed that there was a significant positive relationship between secondary school students' self-efficacy and their academic achievement in ICT. The study further revealed that there was a substantial positive relationship between male secondary school students' self-efficacy and their academic achievement in ICT. It equally shows that there was a significant moderate positive relationship between female secondary school students’ self-efficacy and academic achievement in ICT. Conclusion – Self-efficacy plays a major role in the academic achievement of students in ICT and should not be neglected to improve the academic achievement of students in ICT. Recommendation – Based on these findings, the researchers recommended among others that ICT teachers should encourage students in self-ability through hands-on, minds-on activities for self-reliance, self-development, and societal advancement. Research Implications – The research implications are that learners are drilled on hands-on, minds-on activities for individual development.